West Flemish V3 and the interaction of syntax and discourse - Haegeman, Liliane; Greco, Ciro (The journal of comparative Germanic linguistics, 2018)
The empirical focus of this paper is what looks like a verb third (V3) pattern in West Flemish (WF) in which an adverbial modifier (typically a temporal or conditional adjunct) is followed by a non-inverted subject-initial verb second (V2) root clause. This pattern will be referred to as the non-inverted V3 pattern. This paper has two goals. The first and major aim is to document the WF non-inverted V3 pattern, detailing both its syntactic and its semantic properties, in order to make these data available to the research community at large. We also develop an analysis in line with the hypothesis, substantiated in the paper, that WF is a genuine V2 language and that the apparent V3 data in do not jeopardise this assumption. The core hypothesis is that the initial adjunct in V3 patterns is extra-sentential or 'main clause-external' (cf. Broekhuis and Corver in Syntax of Dutch. Verbs and verb phrases. Volume 3: Chapter 14: main clause-external elements, Amsterdam University Press, Amsterdam, 2016. http://www.oapen.org/), and that it combines with a full-fledged V2 clause by virtue of a discourse-structure (cf. Auer in Pragmatics 6:295-322, 1996). That the non-inverted V3 pattern is not acceptable in all varieties of Dutch is accounted for in terms of microvariation in the syntactic derivation of subject-initial V2 sentences.